Long-term trends in airborne fungal-spore concentrations: a comparison with pollen. (February 2015) - Damialis, Athanasios; Vokou, Despoina; Gioulekas, Dimitrios; Halley, John M.
Abstract: We examined the long-term trends in airborne fungal-spore concentrations in Thessaloniki, Greece, over the period 1987–2005. We estimated trends in the spore levels for the 14 taxa that contribute at least 0.1 % to the total airborne spore concentration. We also tested for trends towards earlier, longer or more highly peaked spore seasons. There was decreasing concentration of spores for 11 of the 14 taxa, especially for Agrocybe, Botrytis, Cladosporium, and Nigrospora, where this trend was significant. Using ANCOVA, there was a highly significant negative trend overall ( p  < 0.001). Regarding the spore-season related attributes, there were very few significant trends. However, the main spore season tended to start later (for 12 of the 14 taxa) and become shorter (for 10 of the 14 taxa); later onset was more pronounced during the most recent part of the study period. Fungi seem to display a delayed and slower response to climate change than plants and in a direction opposite to that of pollen.